Reprentasi Perempuan Pada Film Mars - Lusiana Sinaga; Alemina Br. Perangin-angin (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
The film entitled Mars, directed by Sahrul Gibran, succeeded in attracting the attention of those watching Indonesian films in 2016. This limited screening film tells the story of the role of a mother, wife and breadwinner. This research aims to describe the representation of women in the film Mars. This research uses a qualitative approach with Roland Barthes' semiotic method. Researchers also chose samples based on women's representation. The data collection technique in this research uses documentation techniques. The data in this research are pictures or wordings in the form of representations of women. The primary data source in this research is YouTube. The data collection method used in this research is the observation method using note-taking techniques. The research results show three things that can be put forward as emphasis. Firstly, this film does not emerge from the figure of Tumpon (a weak, steadfast and strong female figure). The second is the struggle of an illiterate mother from a remote village who is struggling so that her daughter can go to school and have a better life than herself. Third, the minimalist and simple cinematic presentation means that every message in this film can be conveyed well because it highlights and depicts the figure of a Javanese woman who lives in poverty, this does not mean that this film carries/speaks of a feminist paradigm or gender justice/injustice.